Chromoblastomycosis caused by Cladophialophora carrionii in a child from India - Pradeepkumar, Narayanappa Shiroorkar; Joseph, Noyal Mariya (The Journal of Infection in Developing Countries, 2011)
Chromoblastomycosis is a chronic fungal infection of the skin and subcutaneous tissue. It usually occurs following trauma with vegetative matter and mainly affects middle-aged male agricultural workers. Only a few cases have been reported in children. The lesions commonly involve the lower limbs, while the upper limbs and face are only rarely affected. We report a case of cutaneous chromoblastomycosis of the left arm, caused by Cladophialophora carrionii, in a 9-year-old boy from India, who was earlier misdiagnosed as cutaneous tuberculosis. The patient showed a good response to treatment with itraconazole and terbinafine.